2010
DOI: 10.1086/652184
|View full text |Cite
|
Sign up to set email alerts
|

Male Circumcision Decreases Acquisition and Increases Clearance of High‐Risk Human Papillomavirus in HIV‐Negative Men: A Randomized Trial in Rakai, Uganda

Abstract: Uncircumcised HIV-negative men aged 15-49 years were randomized to immediate circumcision (n=441) or delayed circumcision (n=399). HPV was detected by Roche HPV Linear Array at enrollment, 6, 12 and 24 months. Incident HR-HPV was estimated in men who acquired a new HR-HPV genotype. HR-HPV clearance was determined in men with prior genotype-specific HR-HPV infections. Rate ratios (RR) and 95% confidence intervals (95%CI) of HR-HPV acquisition were estimated by Poisson multiple regression Enrollment characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
147
6
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(164 citation statements)
references
References 17 publications
8
147
6
3
Order By: Relevance
“…Male circumcision (MC) has been shown to reduce by reduce the risk of sexual HIV transmission from female to male by 60% (http://www.who.int/hiv/topics/malecircumcision/en/index.html) in randomized clinical trials. MC was also associated with a lower incidence of multiple high-risk HPV types and increased clearance of HR-HPVs as compared to controls (14.8% vs 22.3%, respectively) in Uganda (Gray et al 2010); however, MC was not associated with decreased incidence or increased clearance of HR-HPV in the female partners of circumcised men 24 months after the procedure, as compared to partners of men in the control group (Tobian et al 2011) However, MC has long been associated with reduced risk of cervical cancer in the wives of circumcised men; therefore further study is warranted.…”
Section: Primary Prevention Of Hpv/cervical Cancermentioning
confidence: 90%
“…Male circumcision (MC) has been shown to reduce by reduce the risk of sexual HIV transmission from female to male by 60% (http://www.who.int/hiv/topics/malecircumcision/en/index.html) in randomized clinical trials. MC was also associated with a lower incidence of multiple high-risk HPV types and increased clearance of HR-HPVs as compared to controls (14.8% vs 22.3%, respectively) in Uganda (Gray et al 2010); however, MC was not associated with decreased incidence or increased clearance of HR-HPV in the female partners of circumcised men 24 months after the procedure, as compared to partners of men in the control group (Tobian et al 2011) However, MC has long been associated with reduced risk of cervical cancer in the wives of circumcised men; therefore further study is warranted.…”
Section: Primary Prevention Of Hpv/cervical Cancermentioning
confidence: 90%
“…Significantly, the prevalence differences between the 2 groups were not significant for HPV type 16 but were for HPV type 18. Six secondary trials analyzed HIV positive and negative men enrolled in the Ugandan HIV trial with regards to HPV prevalence, acquisition/incidence, clearance and viral load [89][90][91][92][93][94]. The first trial investigated the prevalence of HPV in a subgroup of participants and only included samples from the glans and coronal sulcus, a factor for possible bias due to differential infection sites in circumcised males [89,95].…”
Section: Hpv In Menmentioning
confidence: 99%
“…Recent randomised control trials have reported beneficial effects of circumcision on HPV acquisition and clearance in males in Africa. 82,84,86 However, Van Howe has suggested that these results can be completely explained by sampling bias 87 and has highlighted inadequacies in the methods used for sampling the penis in another study. 80,81 The evidence for whether condoms are a highly effective barrier against transmission of HPV between partners is conflicting.…”
Section: Are Circumcision and Condoms Protective Against Infection?mentioning
confidence: 99%
“…A variety of studies have been conducted to investigate the effectiveness of circumcision in the prevention of HPV infection [78][79][80][81][82][83][84][85][86][87][88] and the interpretation of the findings from these is currently under debate. Recent randomised control trials have reported beneficial effects of circumcision on HPV acquisition and clearance in males in Africa.…”
Section: Are Circumcision and Condoms Protective Against Infection?mentioning
confidence: 99%